Pengaruh Profitabilitas, Likuiditas Dan Solvabilitas terhadap pengungkapan Islamic Social Reporting(ISR) dengan Ukuran Perusahaan sebagai variabel mediasi pada perusahaan yang terdaftar Di Jakarta Islamic Index(JII) tahun 2018-2020 - Sinta Noista Sinta Noista; Mellya Embun Baining; Khairiyani Khairiyani (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2022)
This study aims to determine the effect of Profitability (ROI), Liquidity ((CR), and Solvency (Debt To Asset Ratio) on the disclosure of Islamic Social Reporting (ISR) with company size as a mediating variable in companies listed in the Jakarta Islamic Index (JII). ) period 2018-2020. The population of this study includes all companies registered with JII. The sample was taken by purposive sampling method with certain criteria, during the research period. The data analysis method used in this study was carried out using PLS (Partial Least Square) and data processed using the Smart PLS 3.3.9 program. PLS in this study aims to test the predictive relationship between constructs by seeing whether there is an influence or relationship between research constructs. The results of this study indicate that: (1) Liquidity (CR) has a significant effect on ISR ( 2) the CR variable on Company Size does not have a significant effect on the size of the company company ran (3) DAR variable on ISR has no significant effect on ISR (4) DAR variable on firm size has no significant effect on firm size (5) ROI variable on ISR has a significant effect on ISR (6) ROI variable on firm size has no significant effect on firm size (7) Mediation variable on firm size on ISR has no significant effect on ISR. Keywords: Profitabilitas, Likuiditas, Solvabilitas, ISR, Company Size, Mediating Variabel